A comparative study of 3D printing and heat-compressing methods for manufacturing the thermoplastic composite bone fixation plate: Design, characterization, and in vitro biomechanical experimentation. (December 2021) - Kabiri, Ali; Liaghat, Gholamhossein; Alavi, Fatemeh; Ansari, Mehdi; Hedayati, Seyyed Kaveh
Metallic bone fixations, due to their high rigidity, can cause long-term complications. To alleviate metallic biomaterials' drawbacks, in this research new Glass Fiber/Polypropylene (GF/PP) composite internal fixations were developed, and an investigation of their mechanical behavior was performed through in vitro biomechanical experiments. Short randomly oriented, long unidirectional prepreg, and long unidirectional fiber yarn were considered as reinforcements, and the effects on their mechanical properties of different manufacturing processes, that is, 3D printing and heat-compressing, were investigated. The constructed fixation plates were tested in the transversely fractured diaphysis of bovine tibia under axial compression loading. The overall stiffness and the Von Mises strain field of the fixation plates were obtained within stable and unstable fracture conditions. The samples were loaded until failure to determine their failure loads, strains, and mechanisms. Based on the results, the GF/PP composite fixation plates can provide adequate interfragmentary movement to amplify bone ossification, so they can provide proper support for bone healing. Moreover, their potential for stress shielding reduction and their load-bearing capacity suggest their merits in replacing traditional metallic plates.